Effects of Children's Outdoor Physical Activity in the Urban Neighborhood Activity Space Environment - Yu Bao; Ming Gao; Dan Luo; Xudan Zhou (Frontiers Media S.A., 2021)
The rapid development of cities results in many public health and built-up environmental problems, which have vital impacts on children's growth environment, the development of children, and city contradictions. There is a lack of children being a main concern when constructing new urban areas or reconstructing old districts. Children's activity spaces tend to be standardized and unified (kit, fence, and carpet) "KFC style" designs, which leads to the urban neighborhood space and the environment being insufficient to attract children to conduct activities. Therefore, starting from the urban neighborhood space environment, this paper explores what kind of spatial environment is needed for children's physical activity and its impact on children's physical activity. Taking six residential areas in the Changchun Economic Development Zone as the research object, based on the theory of children's ability development and game value, this paper uses the Woolley and Lowe evaluation tool to quantify the impact of the theory on the urban neighborhood space environment and children's physical activity. It can be confirmed that there is a significant correlation between the spatial characteristics of an urban neighborhood and the general signs of the environment on the duration and intensity of the physical activity of children. The results show that: (1) the differences in children's ages result in differences in the duration and intensity of children's physical activity in the urban neighborhood space environment; (2) the open space factor of the neighborhood space has the most significant influence on the duration of children's physical activity; (3) in terms of the environmental characteristics, whether children can be provided with education and learning opportunities has a significant impact on the duration of children's physical activity; (4) there is a significant positive correlation between children's age and the duration and intensity of the physical activity, exercise type, and imaginative activity. These results show that the urban neighborhood space environment can affect the duration of children's physical activity. In future urban residential area planning and design, urban children can meet the self-demand of physical activity in the neighborhood space through the reasonable balance and combination of neighborhood space characteristics and environmental characteristics.